A Lightweight, Elastic, and Thermally Insulating Stealth Foam With High Infrared‐Radar Compatibility. Issue 35 (26th October 2022) - Gu, Weihua; Ong, Samuel Jun Hoong; Shen, Yuhong; Guo, Wenyi; Fang, Yiting; Ji, Guangbin; Xu, Zhichuan J.
Abstract: The development of infrared‐radar compatible materials/devices is challenging because the requirements of material properties between infrared and radar stealth are contradictory. Herein, a composite of poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) coated melamine foam is designed to integrate the advantages of the dual materials and the created heterogeneous interface between them. The as‐designed PEDOT:PSS@melamine composite shows excellent mechanical properties, outstanding thermal insulation, and improved thermal infrared stealth performance. The relevant superb radar stealth performance including the minimum reflection loss value of −57.57 dB, the optimum ultra‐wide bandwidth of 10.52 GHz, and the simulation of radar cross section reduction value of 17.68 dB m 2, can be achieved. The optimal specific electromagnetic wave absorption performance can reach up as high as 3263.02 dB·cm 3 g −1 . The average electromagnetic interference shielding effectiveness value can be 30.80 dB. This study provides an approach for the design of high‐performance stealth materials with infrared‐radar compatibility. Abstract : A high‐performance infrared‐radar compatible stealth composite is fabricated. The actual radar cross‐section performance is rationally simulated via smart computer simulation technology.